Prenatal differentiation between truncus arteriosus (Types II and III) and pulmonary atresia with ventricular septal defect - K. Traisrisilp (2018)
Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd. Objective To describe antenatal sonographic signs that help in the differentiation of truncus arteriosus Types II and III (TA-II/III) from pulmonary atresia with ventricular septal defect (PA-VSD). Methods From a database of fetal echocardiographic examinations, we identified fetuses with sonographic features of a single great artery with VSD and relatively normal four-chamber view. Records were reviewed, comparing fetuses with TA-II/III and those with PA-VSD, with particular focus on: 1) characteristics of the overriding vessel, 2) appearance of the semilunar valves, 3) competence of the semilunar valves, 4) presence of major aortopulmonary collateral arteries (MAPCA), 5) main pulmonary artery being without antegrade flow, 6) site of arterial branching from the great artery and 7) other minor features, such as cardiac axis or associated anomalies. Results Seventeen fetuses were identified, eight with TA-II/III and nine with PA-VSD. Among the eight fetuses with TA-II/III, seven had abnormal valves and six had valve regurgitation, compared with none of the nine PA-VSD fetuses. Five TA-II/III fetuses had early branching to supply the lungs, whereas most fetuses with PA-VSD had more distal branching. Notably, in six of the TA-II/III fetuses, the root of the single great artery originated predominantly from the right ventricle, while all but one of the PA-VSD fetuses had typical equal overriding of the VSD. The main pulmonary artery was without antegrade flow in two cases with PA-VSD. Finally, four cases with PA-VSD had MAPCA, in two of which this was identified prenatally. Conclusion Identification of abnormal arterial valves or valve regurgitation, site of origin of branching, presence of overriding of the great artery, a main pulmonary artery without antegrade flow and MAPCA are helpful in differentiating between TA-II/III and PA-VSD.